Empowerment of pregnancy care for pregnant women: A concept Analysis - Dewi Hermawati (Idea Nursing Journal, 2019)
Pregnant woman may experience physical discomfort related to pregnancy course as well as the first pregnancy woman that requires them to have empowerments while performing pregnancy care. The empowerment can lead women to enhance ability in caring herself and increasing decision making ability to determine the need of care. This study aim to explore the concept of empowerment in pregnancy care since the concept has not been adequately defining. The method of literature review from books and articles was performed from CINAHL, Sciendirect, and Pubmed with key words such as empowerment, pregnant women, and pregnancy resulted to fifteen related articles which were used to explore the concept based on Walker and Avant (2005) approach of analysis. The result of study yielded four defining attributes of empowerment in pregnancy care including self awareness, competency of knowledge/ skill, ability to take action, and interpersonal relationship. The antecedents including support, personal growth/ experience, and desirable to involve. While the consequences such as being confidence, decision making power, and sense of freedom. The constructions of cases (model, borderline, and contrary) and empirical reference were presented for demonstrating attributes and assessing the existences the concept of empowerment in pregnancy care..Key words: Empowerment, Pregnancy, Concept Analysis